Charges and Maturities-Proposals for Reform. (Policy Papers; Policy Paper ;, 2008)
This paper focuses on two key features of the financial terms and maturities of high access to the Fund's General Resources Account (GRA): surcharges and time-based repurchase expectations. Surcharges, which together with the adjusted rate of charge determine the cost of high access to Fund credit, currently vary across facilities and are linked to either the level of access or the duration of lending. The policy on repurchase expectations is an administrative mechanism that encourages accelerated repayment terms, effectively shortening loan maturities. Both policies on surcharges and repurchase expectations were introduced to mitigate credit risks and safeguard the revolving nature of Fund resources.